Prediction of loss characteristics in built-up areas with variousbuildings' overlay profiles. - Blaunstein, N.
We continue the analysis of a probabilistic approach and the corresponding stochastic multi-parametric model of wave propagation in built-up areas with randomly distributed buildings. We concentrate on the influence of buildings' overlay profiles on signal spatial decay, and on path-loss dependence in the frequency domain within UHF/X-band urban propagation channels. Using different buildings' overlay profiles, the field-intensity attenuation along radio paths is examined, taking into account single-scattering and multiple-scattering phenomena, and diffraction from buildings' corners and rooftops, for various positions of receiver and transmitter antennas with respect to surrounding obstacles. The comparison between experimental and theoretical predictions was motivated by the proposed stochastic multi-parametric model and the experimental data obtained for actual areas in Jerusalem (Israel) and Lisbon (Portugal), as well as by other models of multiple diffraction. The discussion is presented for realistic elevations of both terminal antennas to assess the accuracy and limits of the proposed stochastic model. A sensitivity analysis of the influence on the path loss of built-up terrain parameters and the elevation of antennas relative to the buildings surrounding them is presented.
Keywords: Land mobile radio cellular systems; Land mobile radio propagation factors; Diffraction; Scattering